Effect of horizontal mergers and acquisitions on industry composition : a study of U.S. listed firms. - He, Yuxuan. (2012)
This research explores the effect of horizontal mergers and acquisitions on industry composition. The results show that horizontal mergers and acquisitions have a significant and positive effect on net entrants, consistent with horizontal mergers and acquisitions resulting in positive rents to rival industry players. The results further reveal that the relationship is stronger during times of recession. We find that there is no difference in the relationship between horizontal mergers and acquisitions and the number of net entrants regardless of whether there is deregulation or the industry is highly competitive.